077 Development of an Evidence to Recommendation Table for Guideline Users. (15th August 2013) - Rigau, D; Neumann, I; Sanabria, A; Kristiansen, A; Brandt, L; Vandvik, P; Alonso-Coello, P
Abstract : Background: The DECIDE project aims to improve the dissemination of recommendations using GRADE. Clinical practice guidelines (CPGs) summary tables do not include all the relevant factors for moving from evidence to recommendations: quality of the evidence, balance of benefits and harms, values and preferences and cost. Objectives: Development of an optimal presentation table to inform about the evidence to recommendation (EtR) process to healthcare professionals. Methods: Iterative process including brainstorming and design, user testing with semi-structured interviews, and stakeholder consultation. We analysed the feedback to our initial prototype, defined barriers and facilitators, and generated alternative formats. Results: The table was well rated overall by users. It was found useful to understand in more depth the rationale of the recommendation and of use for teaching sessions. Some users found it potentially useful for shared decision making while others did not find it useful at the point of care. Most frustrations came from misunderstanding some terms, the general purpose of the table or the GRADE system. Discussion: This EtR table could be a useful tool for CPGs users and tabulates all the relevant information beneath the EtR process. We are preparing a second round of user testing and stakeholder consultation, and will present a new format at the conference. Implications for GL Developers and Users: This table will provide users a concise summary of the factors influencing the EtR process. The efficiency of including an EtR table in real CPGs needs to be further evaluated.